The Effect of Teaching Strategies and Learning Styles on the Students’ Achievement - Teguh Satria Amin; Eddi Setia; Lince Sihombing (LINGUISTIK TERAPAN, 2014)
This research investigates 1) students’ achievement in reading comprehension taught by using Direct Reading Thinking Activity (DR-TA) strategy is higher than taught by using Know, What to Learn, and Learned (KWL) strategy, 2) students’ achievement in reading comprehension with impulsive learning style is higher than students’ achievement in reading comprehension with reflective learning style, and (3) there is  interaction between teaching strategies and learning styles on the students’ achievement. Two classes containing of 70 students were chosen as sample by apllying cluster random sampling technique. The experimental group 1 was treated by using DR-TA and the experimental group 2 was treated by using KWL. The students’ achievement was measured by using test. The questionnaire was conducted to find out the students’ learning style. The data were analyzed by applying two-ways analysis of variance. The findings show that (1) the students’ achievement in reading comprehension taught by using DR-TA higher than using KWL; (2) students’ achievement in reading comprehension with impulsive learning style is lower than that with reflective learning style; (3) there is interaction between teaching strategies and learning styles on the students’ achievement in reading comprehension. The analysis revealed that the teaching strategies significantly affected the students’ reading achievement.   Keywords: DR-TA, KWL, Impulsive Learning Style, Reflective Learning Style, Reading Comprehension